Random Verse Method As An Innovation In The Tahfidz Juz 'Amma Program At Mi Sains & Alam Ulul Albab Tulungagung - Fathurrohmah, Arista; Zaenul Fitri, Agus; Agustina Nurlaila Eka Erfiana, Nita; Mufron, Ali; Atirotu Zahroh, Luluk (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
This research is motivated by a phenomenon that occurs in the field, that currently, there are programsimplemented in an institution, not just a way to make progress at the institution, but in marketing efforts so as not to lose competitiveness with elementary school institutions in general. However, this is different from the facts on the ground, namely at the MI Sains & Alam Ulul Albab Maron Boyolangu Tulungagung institution, which actually has a program as a typical institution curriculum that aims to create a new idea that is able to support the learning process of its students, especially in the tahfidz program juz 'amma. Thephenomenon in this institution is the innovation of the tahfidz juz 'amma program, which aims to strengthen students' memorization. So that this is not only able to become a characteristic of the institution's curriculum program itself but also able to become a branding institution that is beneficial to all. The research approach used in this research is a qualitative approach. The type of research used in this research is descriptive research. Data collection techniques using observation, interviews, anddocumentation studies. The data analysis technique uses data reduction, data presentation, and drawingconclusions. In contrast, checking the validity of the data using triangulation techniques, namely sources, techniques, and time. The results of this research showed that: (1) The discovery of the random verse method used in the tahfidz juz 'amma program. The random verse method is a combination that combinesgeneral material as an easy way to memorize and strengthen students' memorization. (2) The distributionof the random verse methods used in the tahfidz juz 'amma program. Delivering to students regarding the new method in the tahfidz juz 'amma program. Conduct socialization and parenting with parents so that they can work together optimally. (3) The absorption of the random verse method used in the tahfidz juz 'ama program. Pay attention to the material that students can understand according to grade level. Build good coordination between institutions and parents to help accompany, support, and monitor student progress. The idea of developing a method for memorizing juz 'amma and the ability of the institution to create a new method as an effort to implement the tahfidz program resulted in a positive point of view for various parties, both for the institution itself, students as implementers, and guardians of students. Thegrowth of the spirit of learning to use new ways in implementing the tahfidz juz 'amma program, because the method used can be easily understood by students. The guardians who know and cooperate with thisinnovation have positive thoughts, especially for the development of their children's tahfidz. Based on thegood responses from various parties, as well as the ability of students who find it easier and more enjoyable to participate in the tahfidz program with this new method, it can be concluded that the innovation of the tahfidz juz 'amma program has been able to strengthen the memorization of the students of MI Sains & Alam Ulul Albab Maron Boyolangu Tulungagung. Purely because of the habit of applying the new method used. Thus, they can be said to be students with strong memorization power in carrying out tahfidz juz 'amma.